THE ASPECT OF SEMIOTIC USING BARTHS THEORY ON BALI WATER PROTECTION ADVERTISEMENT - Ni Putu Novi Lestari (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
This study discusses the denotative and connotative meanings contained in the Bali Water Protection advertisement. Denotation and connotation are part of the semiotic aspect in analyzing the meaning of signs. The analysis of denotation and connotation meaning in this study was based on Barthes' theory. There are two objectives of this study such as: 1To find out verbal and non-verbal signs in Bali Water Protection advertisement, and 2to analyze the signs meaning found in Bali Water Protection advertisement. In this study the data source was taken from Instagram account @Baliwaterprotection and used one advertisement of Bali Water Protection has that used to raise funds. The data were collected by observation methods and used qualitative method to analyzed the data in this study. The data were used theory of signs by Saussure(1983), theory of meaning by Barthes(1987) and used support theory to analysis the color terms by Wierzbicka (1996). This study was analyzed by presenting the verbal and non verbal signs that found in Bali Water Protection into table. The meaning of signs that has in this advertisement were presented in a descriptive way in the discussion. The finding of the analysis show in the advertisement as image and sentence. this study revealed 3 verbal signs, 5 non verbal signs, 1 denotation meaning and 6 connotation meaning from one Bali Water Protection advertisement.